A eletrocoagulação como pré-tratamento de efluente cervejeiro - Costa, Antony Murillo (2020)
The beverage industry, especially the brewery sector, plays a significant role in the country’s and world’s economy, generating jobs and income for the population.However, byproducts and rejects are abundantly generated in the manufacturing process, including the liquid effluent, resulting from the liquid waste from fermentation and beverage production and from cleaning and sterilization process. It’s estimated that for each liter of beer produced from 3 to 10 liters of effluent is generated, which has a high organic and nutrient (N e P) content, harmful if released in natura into the environment. In this context, the aim of this study is investigate the technical and economical feasibility of electrocoagulation process as a pre-treatment for brewery effluent. Iron and aluminum electrodes were analyzed, and after efficiency analysis, it was decided to deepen the research that uses only aluminum electrodes, to achieve higher treatment rates, when compared to iron. In a second step, using the experimental factorial design technique, the factors initial pH, treatment time, potential difference applied and amount of electrolyte added were investigated. The parameters were monitored: final pH, turbidity (TU), chemical oxygen demand (COD), total sugars (ST), phosphorus (P), residual aluminum (RAL) and total solids (TS). Maximum removals of 61% for TU (pH0 7, 40 minutes, 12 V, 3 g/L of electrolyte), 35% for COD (pH0 7, 40 minutes, 12 V, 0 g/L of electrolyte), 57% for ST (pH0 5, 20 minutes, 6 V, 3 g/L of electrolyte) and 100% for phosphorus (multiple cases). However, the process promotes an increase in pH0 and the amount of TS. In a third step, the reduction of the intra-electrode spacing was tested, adopted to increase the current density, without changing the voltage, and including aeration at the bottom of the reactor, to facilitate the sludge flotation. It was concluded, in this case, that the aeration does not add significant gains to the process, while the reduction of spacing does. However, the excessive approach of the electrodes did not generate satisfactory results. With the optimization of the operating parameters, kinetic tests were performed, and behavioral curves of the parameters pH, applied current, conductivity, P, TU, RAL, COD and ST were elaborated. P and TU removal rates stabilized after 25 min of operation and COD and ST rates after 3 min. In kinetic tests, the maximum removal rates obtained were 59% of TU, 96% of P, 19% of COD and 36% of ST. The best cost/benefit of operating was reached at 25 minutes, with 0.836 R$/kgCOD removed and 0.146 R$/gP removed (0.208 US$/kgCOD and 0.036 US$/gP). It was concluded that the electrocoagulation process is a viable alternative for pretreating the studied brewing effluent, with excellent removal of total phosphorus, with low operating cost, reducing, in this case, the need for subsequent complex treatments.